LINC00339 accelerates invasion and migration of colorectal cancer via mediating miRNA-30a-5p: LINC00339 accelerates the progression of colorectal cancer - Zhou, Peng; Wu, Jie; Zheng, Zihan; Liao, Chuanwen; Sun, Xuejun (Cellular and Molecular Biology, 2023)
To analyze the biological function of LINC00339 in the progression of colorectal cancer (CRC). We aim to provide directions in the early-stage treatment of CRC. LINC00339 level in 60 paired CRC tissues and paracancerous tissues was examined by quantitative real-time polymerase chain reaction (qRT-PCR). The correlation between the LINC00339 level and clinical parameters was analyzed. Moreover, the LINC00339 level in CRC cell lines was determined as well. LINC00339 expression was changed in HCT-8 and HCT-116 cell lines by transfection of LINC00339 overexpression plasmid or anti-LINC00339. The regulatory effects of LINC00339 on the migratory and invasive abilities of CRC cells were evaluated through a series of functional experiments. Dual-luciferase reporter gene assay and rescue experiments were conducted to verify the interaction of LINC00339 and miRNA-30a-5p in mediating the progression of CRC. LINC00339 was upregulated in CRC tissues relative to paracancerous tissues. CRC patients with higher levels of LINC00339 had higher rates of lymph node metastasis and distant metastasis, and worse prognosis than those with lower levels. Knockdown of LINC00339 attenuated migratory and invasive abilities of HCT-116 cells. Overexpression of LINC00339 in HCT-8 obtained the opposite trends. In addition, we verified a negative correlation between LINC00339 and miRNA-30a-5p in CRC tissues. LINC00339 served as a ceRNA to absorb miRNA-30a-5p. Rescue experiments confirmed that miRNA-30a-5p knockdown revered the regulatory effects of LINC00339 on the migratory and invasive abilities of CRC cells. LINC00339 was closely correlated to metastasis and poor prognosis of CRC. It accelerates CRC cells to migrate and invade via mediating miRNA-30a-5p.